PROBABILITY DISTRIBUTION FUNCTIONS OF RANDOM VARIABLES - Kayumov Shukur; Ziyadullaeva Shakhlo; Mamadiyarov Sardorbek; Turgunbaev Asadulla (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
Abstract: to characterize the properties of random variables in probability theory, the concept of the probability distribution law of a random variable is used. The probability distribution law provides complete information about the properties of a random variable and allows one to obtain the probabilistic value of the measured quantity and the characteristics of the random error. The main characteristics of the probability distribution laws of random variables are the integral and differential distribution functions and the numerical characteristics of the position, dispersion, asymmetry and excess of probability distributions.